Effect of molar mass on film-forming properties of self-crosslinking latexes based on structured acrylic microgels - Machotová, Jana; Podzimek, Štěpán; Kvasnicka, Pavel; Zgoni, Hedvika; Šňupárek, Jaromír; Černý, Michal (Elsevier Science BV, 2016)
The influence of molar mass of the shell layer of latex particles having core-shell morphology on film forming and final coating properties of self-crosslinking latexes based on keto-hydrazide crosslinking system was investigated. Structured latex particles were prepared by the semi-continuous non-seeded emulsion polymerization of acrylic monomers. The particle core was slightly crosslinked to prevent the copolymers forming the core phase from migration into the shell phase. The molar mass of copolymers forming the shell phase was gradually reduced by isooctyl 3-mercaptopropionate chain transfer agent included in the synthesis of the shell layers. The results confirmed theoretical predictions and revealed that even a slight amount of chain transfer agent added during the synthesis achieved a substantial lowering of minimum film-forming temperature and reduction of water sensitivity of latex coatings.
Vliv molekulové hmotnosti na formotvorné vlastnosti samosíťujících latexů na bázi strukturovaných mikrogelů
Keywords: Emulsion polymerization; Core-shell latex; Molar mass distribution; Diacetone acrylamide; Emulzní polymerace; core-shell latex; distribuce molekulové hmotnosti; diacetonakrylamid